Protein Extract of Tobacco Expressing Solanum torvum PP5-Encoding Gene Inhibits Verticillium dahliae Proliferation - Min Chen; Chao Xie; Qing Yang; Wenjiao Zhu; Man Wang (Horticulturae, 2022)
Verticillium wilt, a soilborne disease caused by Verticillium dahliae (V. dahliae), can severely affect the yields of Solanaceae crops. In a previous study, it was observed in Solanum torvum (S. torvum) that protein phosphatase 5 (PP5) was induced by V. dahliae infection. To elucidate the function of PP5 more clearly, this study cloned an StPP5 cDNA from S. torvum by PCR. The cDNA contained an ORF of 1458 bp long encoding a putative protein of 485 amino acid residues with a predicted molecular mass of 54.63 kDa and a theoretical isoelectric point of 5.66. StPP5 protein contained a conserved PP domain and showed high similarity to other homologous members of the PP5 family from various plant species. The expression of StPP5 gene was upregulated after V. infection and reached its maximum value at 24 h in leaves. In order to clarify the role of StPP5, four transgenic tobacco plants expressing StPP5 were generated through Agrobacterium-mediated transformation and identified by PCR. In vitro culture assay showed that the growth of V. dahliae in PDA medium containing proteins extracted from the leaves of transgenic tobacco line P6 was inhibited, whose inhibition rate was 55.1%, higher than the non-transgenic control. These results indicated that StPP5 might be involved in plant defense against V. dahliae infection.